Morphological and Palynological Systematic Study of Genus Borage (Borago officinalis L.) Family Boraginaceae in Kurdistan-Iraq - Rupak Towfiq Abdulrazaq (International Journal of Medical Toxicology and Legal Medicine, 2024)
The genus Borago L. with one wild speciesBorago officinalis L. Family Boraginaceae in Kurdistan has beeninvestigated systematicallyabout their morphological and palynological traits. Phytogeographic districts were surveyedto collect plant specimens and know their distribution. Among the morphological characters; the leaf, flower,inflorescence and fruit were important together in the identification of this species ,while the properties of calyx, corolla andpods were the most effective for that. The pollen traits such as shape, diameter and configuration were contributed inidentification of pollens which were found to be colporate.The new findings of this study are that the taxon of thisgenus which was recorded in the flora of Iraq was fully described for their morphological, (LM) palynologicaltraits for the first time.